2019
DOI: 10.3389/fpsyt.2019.00289
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Sex-Specific Effects Based On Emotion- and Cognition-Related Behavioral Assessment of Adult Rats After Post-Traumatic Stress Disorder From Different Lengths of Maternal Separation

Abstract: Adverse early life stress is a major cause of vulnerability to various mental disorders in adulthood, including post-traumatic stress disorder (PTSD). Recent studies have suggested that early life stress can help the body adapt optimally when faced with stressful trauma in adult life. An interaction may exist between early life stress (e.g., childhood trauma) and vulnerability to PTSD. This study aimed to evaluate emotion-related behaviors and verify the long-lasting effects of cognitive aspects of PTSD after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 56 publications
3
14
0
Order By: Relevance
“…The study also reported decreased dendritic spine density in the prefrontal cortex (dorsal agranular insular cortex—AID) and increased densities in the hippocampus CA1 area in adult male rats ( de Melo et al, 2018 ). However, our data support the results from a study by Yang et al (2019) , suggesting that rats exposed to stress early in life, via daily maternal separation from PD 2 to PD 14 for 3 or 6 h, had decreased anxiety-like behaviors ( Yang et al, 2019 ). Our data agree with a study by Borges-Aguiar et al (2018) , where 3 h of daily maternal separation during the entire lactation period failed to affect anxiety behaviors in adult rats in the EPM or OF.…”
Section: Discussionsupporting
confidence: 91%
“…The study also reported decreased dendritic spine density in the prefrontal cortex (dorsal agranular insular cortex—AID) and increased densities in the hippocampus CA1 area in adult male rats ( de Melo et al, 2018 ). However, our data support the results from a study by Yang et al (2019) , suggesting that rats exposed to stress early in life, via daily maternal separation from PD 2 to PD 14 for 3 or 6 h, had decreased anxiety-like behaviors ( Yang et al, 2019 ). Our data agree with a study by Borges-Aguiar et al (2018) , where 3 h of daily maternal separation during the entire lactation period failed to affect anxiety behaviors in adult rats in the EPM or OF.…”
Section: Discussionsupporting
confidence: 91%
“…Also, we found that female respondents have more negative alterations in cognition or mood sub-symptoms than males. There has been no evidence to suggest the reason for the difference, but animal studies have shown different mood changes in rats of different genders, with female rats showing stronger emotional changes than male rats (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hormone levels in ovaries are responsible for impaired response to stimulate emotion in some cycles from the menstruation process that may form a particular psychological vulnerability in women(Soni et al, 2013 ). Yang et al showed that female participants experienced the most adverse effects in symptoms of cognitive function or feeling than men (Yang et al, 2019 ). Experimental research showed that in nervous systems related to worry and excitement, women were more reactive than men (Felmingham et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%